Nutrient Use Efficiency: From Basics to Advances 2014
DOI: 10.1007/978-81-322-2169-2_8
|View full text |Cite
|
Sign up to set email alerts
|

Nitrification Inhibitors: Classes and Its Use in Nitrification Management

Abstract: The explosive expansion of human activity during the last two centuries through industrial and agricultural pursuits has resulted in massive changes in the nitrogen (N) cycle of the planet. Based on the projected population growth and food demand, the N-fertilizer inputs into agricultural systems need to be doubled in the near future which would lead to further increase in the amount of N lost to the environment. If production agriculture continues to move towards high-nitrification agricultural systems with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…In addition, N 2 O production through denitrification of nitrate released during nitrification is also reduced when nitrification is inhibited. (Slangen and Kerkhoff, 1984;Chien et al, 2009;Trenkel, 2010;Kumar et al, 2015):…”
Section: Types Of Nitrification Inhibitormentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, N 2 O production through denitrification of nitrate released during nitrification is also reduced when nitrification is inhibited. (Slangen and Kerkhoff, 1984;Chien et al, 2009;Trenkel, 2010;Kumar et al, 2015):…”
Section: Types Of Nitrification Inhibitormentioning
confidence: 99%
“…Overview of nitrification inhibitors (Trenkel, 2010;Kumar et al, 2015). (Bronson et al, 1992) 4-amino-1,2,4-6-triazole-HCl ATC Ishihada Industries (Malhi & Nyborg, 1988) 2,4-diamino-6-trichloromethyltriazine Cl-1580 American Cyanamid (Bremner & Yeomans, 1986) Dicyandiamide DCD Showa Denko y (Treweek et al, 2016) Thiourea TU Nitto Ryuso (Malhi & Nyborg, 1988) 1-mercapto-1,2,4-triazole MT Nippon No recent reference 2-amino-4-chloro-6-methylpyramidine AM Mitsui chemicals (Kumar et al, 2015) 2-sulfanilamidothiazole ST Mitsui Chemicals (Bremner & Yeomans, 1986) (Menéndez et al, 2012) 1-amide-2-thiourea ASU Nitto Chemical Ind.…”
Section: Table 15mentioning
confidence: 99%
See 2 more Smart Citations
“…The seed cake and extracts of Mahua contain alkaloids called saponin which slow down the N mineralization through nitrification inhibition. Based on the incubation study conducted on clay loam soil Kumar et al, (2015) found that the nitrification inhibitory effect of mahua cake extract persisted only for 20 days. The advantages of NNI are easily available, cheap, and eco-friendly (Upadhyay et al, 2011).…”
Section: Natural Nitrification Inhibitors (Nnis)mentioning
confidence: 99%